'This looks like a job for an accountant! (with good funeral insurance)': The changing roles of accountants in superhero comics from 1938 to 2018. (February 2021) - Rocher, Sébastien; Christensen, Mark; Roy, Yves
The roles of accountant characters in a coherent genre of entertainment media, and over time, remain surprisingly under-researched. In this study, it is argued that the roles of accountants in society can be interpreted from longitudinal analyses of the roles played by accountant characters in entertainment media narratives depicting fictional worlds. Analysis is provided of narratives in which actantial and thematic roles are played by accountants in 178 US superhero comics' narrative sequences between 1938 and 2018. The sequences were those in which at least one character is presented as an accountant. The study reveals that accountants have increasingly been portrayed in more positive than negative roles since the beginning of the twenty-first century and have become symbolic superheroes. At the same time, this study also shows that individual accountants do not last long in these narratives, even though they have a positive role. This article shows how one genre of entertainment media has conveyed an improved image of accountants in fictional worlds, to give them progressively a place of importance comparable perhaps to the one that their professional bodies argue they occupy in modern society. Even if some negativity is still attached to the accountant, their image is progressively changing for a better one based on the roles they played because they are accountants.